Synthesis of New Highly Functionalized Quinolines via a Novel FeIII-Catalyzed Domino aza-Michael/Aldol/Aromatization Reaction - Heckmann, Felix; Ibrahim, Mohammad M.; Hampel, Frank; Tsogoeva, Svetlana B. (Synlett, 2024)
We report the development of a straightforward, waste-reducing, environmentally friendly, FeIII-catalyzed domino aza-Michael/aldol/aromatization reaction in the presence of water to access high-value functionalized quinolines by using 2-aminobenzophenones and ethyl buta-2,3-dienoate as starting compounds. The tangible advantages, that is, the utilization of commercially available and/or easily accessible substrates, simplicity, mild reaction conditions, and application of water as a solvent, make this three-step domino process green and highly appealing for the direct construction of a wide variety of highly functionalized quinolines in up to 78% yield.
Keywords: domino reactions; Fe catalysis; Lewis acid catalysis; quinoline synthesis; sustainability